Timing of Work‐Rest Implementation Influences Worker Productivity Under Heat Stress: Evidence for Initial Stay Time‐Based Scheduling - Glen P. Kenny; Kelli E. McCormick; Katie E. Wagar; Roberto C. Harris‐Mostert; James J. McCormick; Leonidas G. Ioannou; Fergus K. O'Connor (American Journal of Industrial Medicine, 2026)
ABSTRACT Introduction Work‐rest allocations recommended by the American Conference of Governmental Industrial Hygienists (ACGIH) limit heat strain and are typically implemented from the onset of work. Whether delaying implementation until after the initial stay time (IST; the duration of continuous work before core temperature reaches 38.0°C) improves total work performed is unknown. Methods Young males performed moderate‐ (200 W·m −2 ) and heavy‐ (260 W·m −2 ) intensity work at a wet‐bulb globe temperature 26°C (34.1°C, 35% relative humidity). Two work protocols were compared using independent cohorts (moderate: n = 15 per cohort; heavy: n = 10 per cohort): Protocol A, IST‐guided delayed work‐rest implementation and Protocol B, standard ACGIH work‐rest implementation consisting of moderate: 45‐min work, 15‐min rest; heavy: 30‐min work, 30‐min rest. Trials consisted of 240‐min morning and afternoon work periods separated by a 1‐h lunch break. Results During moderate work, total work time was greater with Protocol A in the morning (+24 min, 95% CI: 13–36, p < 0.001), with no difference in the afternoon (0 min, 95% CI: −12 to 12, p = 0.994). During heavy work, morning work time was also greater with Protocol A (+30 min, 95% CI: 22–38, p < 0.001), with no afternoon difference (+7 min, 95% CI: −1 to 15, p = 0.081). Time above 38.3°C did not differ during moderate work ( p = 0.252) and was lower during heavy work (−24 min, 95% CI: −44 to −4, p = 0.017). Conclusion Delaying work‐rest cycles until after IST increases morning work output by ~10%–13% without increasing time above critical core temperature thresholds.